2020
DOI: 10.1080/17483107.2020.1841836
|View full text |Cite
|
Sign up to set email alerts
|

Robot dramas may improve joint attention of Chinese-speaking low-functioning children with autism: stepped wedge trials

Abstract: Introduction: Children with autism spectrum disorder (ASD), especially those with low cognitive functioning, have deficits in joint attention. Previous research has found that these children are interested in engaging with social robots. Purpose:In the present study, we designed a robot drama intervention for promoting responses to joint attention abilities (RJA) of children with low-functioning autism (IQs < 70). Materials and methods: Using a stepped wedge design, Chinese-speaking children aged six to eight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 54 publications
0
8
1
Order By: Relevance
“…It is foreseeable that in the coming years, many professionals in the health sector will have to deal with these devices through new working models based on SRs [26,27]. These systems involve and will involve figures who have to do with the elderly [6][7][8][9], frail, and handicapped individuals with motor and communication problems [10][11][12][13][14][15]. These systems involve and will involve figures who have to do with the elderly, frail, and handicapped individuals with motor and communication problems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is foreseeable that in the coming years, many professionals in the health sector will have to deal with these devices through new working models based on SRs [26,27]. These systems involve and will involve figures who have to do with the elderly [6][7][8][9], frail, and handicapped individuals with motor and communication problems [10][11][12][13][14][15]. These systems involve and will involve figures who have to do with the elderly, frail, and handicapped individuals with motor and communication problems.…”
Section: Discussionmentioning
confidence: 99%
“…We can use SRs for a variety of purposes; for example, as educational tools and therapeutic aids [2,3]. There are several examples of SRs designed for use by elderly people [6][7][8][9] but also for frail and/or handicapped subjects needing rehabilitation and assistance: for example [10][11][12][13][14][15], to support certain motor activities; support during feeding; support during displacements; support them in drug therapy-for example, by reminding them to take a drug; support them from a cognitive point of view-for example, by stimulating them with games and supporting them from the point of view of communicative interaction, even as simple company; provide support as a hospital assistant; provide support as a mediator to therapists and/or relatives.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to RJA, the IJA ability of all children was enhanced and maintained over time despite IJA not being explicitly taught. While So et al (26,28) reported effective learning outcomes of robotic intervention in their previous studies, they did not include the human intervention condition for comparison.…”
Section: Open Accessmentioning
confidence: 99%
“…To sum up, researchers have not yet reached a consensus on the effectiveness of robots in improving JA in children with ASD. While So et al (26,28) found positive learning outcomes of robot dramas, they did not include human-based intervention for comparison of learning effectiveness. Additionally, very few studies examined whether robotic intervention is more effective than human intervention in promoting JA (25,30,31).…”
Section: Open Accessmentioning
confidence: 99%
“…(f) Support in the rehabilitation therapy of communication disabilities such as autism or others, where the robot can represent a useful tool full of stimuli for children [18,[21][22][23][24][25][26][27][28].…”
Section: Social Robotsmentioning
confidence: 99%